Authentication Scheme using RFID for Healthcare Applications - BACHIRI, Achouak; LEMOUNES, Ahlam (UNIVERSITY of M'SILA, 2022)
Radio frequency identification (RFID) technology has been used to build improved healthcare systems in recent years, providing a variety of healthcare services that can benefit both medical staff and patients. However, because RFID systems use unsecure communication routes, security is a major concern that must be addressed before RFID can be deployed in healthcare systems. The major goal of this project is to develop a better RFID authentication protocol that ensures security. We improved a pervious Protocol Agrahari et al. that was based on ECQV with a new algorithm kyber.CPA PKE that considered as a candidate in NIST post quantum cryptography standardization NIST post-quantum cryptography standardization. We used kyber.CPA PKE which consisting of key generation, encryption and decryption algorithm for achieve our goal and to overcome these weaknesses that existing before. The security of our scheme is confirmed with security analyses Based on several metrics. Besides, it is compatible with low-cost RFID tags. Moreover, our protocol achieves better performance and it fulfils the basic requirements. Thus, the suggested protocol is capable of providing excellent security for RFID-based healthcare systems.
Keywords: Authentication, healthcare system, RFID, security.